Penilaian Kesehatan Koperasi pada Koperasi Sawit Makmur Berdasarkan Petunjuk Teknis Deputi Bidang Perkoperasian Nomor 15 Tahun 2021 - Ines Saraswati Machfiroh; Jaka Permadi; Widiya Astuti Alam Sur; Rehgetah Permata Putri (Jurnal Akuntansi, 2022)
This research aims to assess the health of cooperatives in the financial performance aspect of the Sawit Makmur Cooperation based on the Technical Instructions of the Deputy for Cooperation Number 15 of 2021. The method used in this research is descriptive qualitative, the data used in this study is quantitative in the form of numbers contained in in the Accountability Report of the Management and Superintendent of the Sawit Makmur Cooperation for the 2021 Fiscal Year. The results of the research on the assessment of the health of cooperation in the financial performance aspect of the Sawit Makmur Cooperation are based on the Technical Instructions of the Deputy for Cooperation Number 15 of 2021 which are reviewed from 3 aspects, namely: evaluation of financial performance, management financial sustainability and financial sustainability that the sound level of the Sawit Makmur Cooperation is in the "fairly healthy" predicate with a score of 67.10. The implication of this research is that an assessment of the health of the cooperative's financial performance can be used as a comparison between the results and the strategies implemented by the cooperative, which can then be used as a means of making improvements and planning future strategies.Keywords: Health Cooperation, Technical Instructions Number 15 of 2021, Financial